A (in)evitável didatização do livro infantil através do livro didático - Ana Maria da Silveira Bossi (2000)
The didactic process of texts adapted from children books present in teaching reading literacy was the mainly purpose of this research wich proposed the transformation of graphic, textual, linguistics, contextual in these texts according the students education. Analysing the beginning twelve books of teaching reading literacy presented in Guia dos livros didáticos 1º a 4º séries. PNLD/98all the texts presented for reading activities were classified according their original supports showing in different kinds of texts more number of texts adapted from children books, collowed by didactic texts written bythe autors of the didactics books and texts dapted from folklore and oral tradition, newspapers, magazines and other material presented in our social community. Choosing the children books we can established that they provide more poetry than narrative and other types of texts wich allowed us the prove that poetries are more didactic for being short and represent singular metrical sounds of the words so they are more switable for beginners in the teaching reading litaracy process. According to the didactics children books selected by the authors of teaching reading literacy , a new choose was made by them and the texts more didactic were the corpus of the analyse, in the case, the texts of the poet Vinícius de Moraes and the narrator Ana Maria Machado, followed by two authors Elias José and Ruth Roch, that confirmed the same rules presented in the didactic books of the first ones. The analysed showed that the texts alteration occur more in discursive context and they become an educational text and the purpose of the texts in the books of teaching reading literacy modifies its readinf because of the activities that are presented as model to be used in the classroom based on the written system and the graphic transformation ser because of the change of printing, modifying the way the texts that are presented to be read, as they are in the didactic books, the textual modification was less in poems wich are presented according to their integral form and more in the textual narratives wich were shortened and modified. We can observe allthough contrarily that the narratives present better purpose of work than poems and we can see that in the didactic transposition the characteristics are rejected in these texts wich identify them in artistic manner: author, style, epoch, historical and social context, gender and language.